Predefined-time cooperative output regulation for second-order nonlinear multiagent systems with an unknown exosystem via dynamic gain method - Jin, Zengke; Wang, Chaoli; Liang, Dong; Liang, Zhenying; Li, Shihua (Neurocomputing (Amsterdam), 2024)
The predefined-time cooperative output regulation of second-order nonlinear multiagent systems with an unknown exosystem is investigated in this paper. Existing similar work is almost limited to exactly known exosystems, and the upper bound of convergence time for closed-loop systems is difficult to adjust and predict, which may not meet practical needs. In this paper, we first propose a new dynamic compensator called predefined-time distributed observer, which guarantees that each agent estimates the state and parameters about the linear exosystem with unknown system matrix through the general directed communication network within the time set by an explicit parameter. Subsequently, combining the improved dynamic gain control method and the proposed predefined-time distributed observer, a novel distributed dynamic predefined-time control scheme is proposed, which solves the problem of this paper by simplifying the tedious arithmetic process caused by the traditional backstepping method. The final simulation experiments verify the effectiveness of the proposed control scheme. •We extended similar articles to more general leader and controlled objects.•The settling time of our controller can be set directly and structure is simple.•We present a new distributed observer for unknown leader and general digraph.•The designed observer can work for an arbitrarily set period of time.•We transform an unknown leader into a known one in a predefined time.